2019
DOI: 10.1029/2019ja026839
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Spatiotemporal Morphology of Plasma Bubbles Based on EAR Observations

Abstract: Spatiotemporal characteristics of equatorial plasma bubble (EPB) have been studied based on Equatorial Atmosphere Radar (EAR) fan sector observations from Kototabang. EPBs were characterized as either locally generated (whose genesis and subsequent evolution was observed in the fan sector maps) or drifted type (which drifted into fan sector scans from west). Investigation of the radar echo spectral width indicated that the drifted EPB could be less evolving type. Height of the F layer in the postsunset period … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 61 publications
(107 reference statements)
0
1
0
Order By: Relevance
“…However, these authors have not used any proxy parameters to identify and confirm the evolving or drifted-in EPBs. Recently, based on radar echo spectral width, Joshi et al (2019) suggested that the drifted-in EPBs are less evolving type. In the present case, the signal is transmitted from geostationary satellite.…”
Section: Estimation Active Phase Duration Of Fesfmentioning
confidence: 99%
“…However, these authors have not used any proxy parameters to identify and confirm the evolving or drifted-in EPBs. Recently, based on radar echo spectral width, Joshi et al (2019) suggested that the drifted-in EPBs are less evolving type. In the present case, the signal is transmitted from geostationary satellite.…”
Section: Estimation Active Phase Duration Of Fesfmentioning
confidence: 99%